Risk Analysis of Placenta Previa in Subsequent Pregnancy with History of Cesarean Section: A Case Control Study in Faridpur Medical College Hospital (Faridpur Medical College Journal, 2016)
Placenta previa is a life threatening pregnancy complication where placenta partially or completely covers the internal cervical os causing serious adverse consequence for both mother and baby. History of cesarean delivery is an important risk factor for placenta previa. Which have a increased chance of cesarean hysterectomy and bladder injury because of an associated accrete syndrome. The objective of this study is to analyze the outcome of placenta previa with history of cesarean section. This is a prospective study done in Faridpur Medical College Hospital, Bangladesh from 01.01.2013 up to 31.12.14. Total 18 (study group) patients had undergone cesarean delivery with placenta previa and history of previous cesarean section. Among 18 patients maternal age range was 25- 40, parity 1-4, emergency hysterectomy was done in 11, average blood transfusion 2-8 and other morbidity like urinary bladder injury was 4. So we decided to conduct the study to evaluate the frequency of the placenta previa and morbidity related to number of previous cesarean deliveries.Faridpur Med. Coll. J. Jul 2015;10(2): 52-54